Global Financial System Resilience: Assessing Vulnerabilities and Safeguards (Journal of Informatics Education and Research, 2024)
This study examines the complex relationships that exist between sustainability, the global financial system, and Environmental, Social, and Governance (ESG) problems. With an emphasis on sustainable financing, it looks at how ESG components affect the financial system's resilience. The research indicates that financial decision-making processes are increasingly taking ESG factors into account. This demonstrates how crucial it is to match financial procedures with environmental goals. The paper discusses how, despite credit rating agencies giving utmost priority to financial strength, the financial sector is becoming more and extra focused on sustainability. It also discusses the difficulties in adding long-term sustainability issues, including climate change, into credit ratings. The need for a more secure and sustainable global financial system is highlighted by this study's illumination of the shifting ESG landscape, the function of financial institutions, and the standards for evaluating corporate sustainability.